Analysis of Criminal Punishment of Perpetrators of The Criminal Act of Theft with Aggrevaction from The Perspective of Legal Certainty (Study of Decision Number 126/Pid.B/2024/PN Pml) - Marpaung, Marzuki Joshua; Laksana, Andri Winjaya (UNISSULA Semarang, 2025)
This study aims to analyze the legal aspects of the crime of aggravated theft in the context of social justice, focusing on Case Number 47/Pid.B/2022/PN Lbo. This study examines the application of criminal sanctions to the perpetrator and considers the judge's perspective in issuing the verdict. The research problem formulation covers two main aspects: first, how criminal sanctions are applied in this case, and second, how the judge's considerations reflect the values of social justice. This study uses a descriptive analysis method to explore the legal aspects of the crime of aggravated theft, focusing on Case Number 47/Pid.B/2022/PN Lbo. The research findings demonstrate the importance of a social justice-based approach to law enforcement, which focuses not only on punishment, but also on rehabilitation and crime prevention, to create a fairer and more effective justice system.